A History of Disease in Ancient Times - Norrie, Philip. author. aut Link
XV, 155 p. 16 illus. in color.
Keywords: This book shows how bubonic plague and smallpox helped end the Hittite Empire, the Bronze Age in the Near East and later the Carthaginian Empire. The book will examine all the possible infectious diseases present in ancient times and show that life was a daily struggle for survival either avoiding or fighting against these infectious disease epidemics. The book will argue that infectious disease epidemics are a critical link in the chain of causation for the demise of most civilizations in the ancient world and that ancient historians should no longer ignore them, as is currently the case.